2007
DOI: 10.2214/ajr.07.2423
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging and Tractography of Median Nerve: Normative Diffusion Values

Abstract: The normative diffusion values of the human median nerve can be used as a reference in evaluation, diagnosis, and follow-up of entrapment, trauma, and regeneration of the median nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 18 publications
6
132
1
2
Order By: Relevance
“…Tracking of fibers automatically started when the FA values of the voxels was above a threshold of 0.15 and was terminated at a threshold value of 0.35 or if the fiber angulation exceeded more than 55°. Similar reconstruction parameters were used in previous studies [1,6].…”
Section: Mr Imagingmentioning
confidence: 96%
See 2 more Smart Citations
“…Tracking of fibers automatically started when the FA values of the voxels was above a threshold of 0.15 and was terminated at a threshold value of 0.35 or if the fiber angulation exceeded more than 55°. Similar reconstruction parameters were used in previous studies [1,6].…”
Section: Mr Imagingmentioning
confidence: 96%
“…Recently, several pilot studies with regard to the application of diffusion tensor imaging (DTI) and fiber tractography to peripheral nerves, e.g., the median, radial, and ulnar nerve at the wrist, the peroneal and tibial nerve at the knee/calf/ ankle, as well as the sciatic nerve, have been published [1][2][3][4][5][6]. Possible clinical applications include the evaluation of peripheral nerves in compressive neuropathies such as the carpal tunnel syndrome or tracking of peripheral nerves in the presence of malignant neoplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWI has been widely used for clinical applications in evaluation of the central nervous system for the diagnosis of diseases such as acute brain stroke [14]. Recently, it has been reported that DWI is useful for the evaluation and diagnosis of lesions such as multiple sclerosis [15,16] and peripheral nerve compression disorders such as carpal tunnel syndrome [17][18][19], using diffusion values such as ADC. An increase in the mean diffusivity (ADC) values was observed in injured nerves with demyelination [15,16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that DWI is useful for the evaluation and diagnosis of lesions such as multiple sclerosis [15,16] and peripheral nerve compression disorders such as carpal tunnel syndrome [17][18][19], using diffusion values such as ADC. An increase in the mean diffusivity (ADC) values was observed in injured nerves with demyelination [15,16,19,20]. Imaging of the spinal cord is challenging because of technical limitations such as the relatively small size of the cord, susceptibility artifacts because of tissue-bone interfaces, and the motion artifacts arising from respiratory activity [21].…”
Section: Introductionmentioning
confidence: 99%